Framework on evaluation and selection of ERP systems - Chang, Hsin Mun (2008)
Many companies have implemented Enterprise Resource Planning (ERP), expecting ERP to solve Y2K problems and provide a complete integration of different business processes. However, not all implementations were successful. Were such problems due to poor pre-implementation evaluation of ERP? What framework should organizations adopt in evaluating ERP? By reviewing academic journals and case studies of other organizations, we shall outline a framework for a pre-implementation evaluation of ERP.